The End of Nature: Between Disenchantment of the World and New Mythologies - Daraškevičiūtė, Vaiva (Filosofia, 2019)
In this article, the situation of the end of nature is discussed in the terms of the Weberian metaphor ‘the disenchantment of the world’ and its variations. The nostalgic effort to return to nature is explained referring to the Romantic notion of nature and the peculiar reiteration of nostalgic utopia in our times (see the example of ancient Lithuanian feasts). In addition to that, the article analyses the contrasting approach which is also characterized by the negative valuation of exploitive relation towards nature. However, in this second case, the reaction to the situation of the end of nature is based on a radical reformulation of the concept of human. According to this model, the relationship with nature should refuse the anthropocentric perspective. In this article, this position is described as a disenchantment of human and is illustrated by artistic performance, which aims to demonstrate the commensurability of human and animal on the bodily level.